Associations and interaction effects of maternal smoking and genetic polymorphisms of cytochrome P450 genes with risk of congenital heart disease in offspring: A case–control study. Issue 23 (11th June 2021) - Diao, Jingyi; Zhao, Lijuan; Luo, Liu; Li, Jinqi; Li, Yihuan; Zhang, Senmao; Wang, Tingting; Chen, Letao; Huang, Peng; Qin, Jiabi
Abstract : Abstract: To assess associations and interactions of maternal smoking and cytochrome P450 (CYP450) genetic variants with the developments of congenital heart disease (CHD) and specific subtypes. A case–control study of 654 cases and 666 controls was conducted from November 2017 to March 2020. The exposures of interest were maternal active and passive smoking before/in the early pregnancy and CYP450 genetic polymorphisms. Data were analyzed using the Chi-square test and logistic regression analysis. After adjusting for the potential confounding factors, our study showed maternal active (ORadj = 2.34, 95%CI: 1.19–4.60) or passive (ORadj = 1.76, 95%CI: 1.34–2.31) smoking before pregnancy, passive smoking in the early pregnancy (ORadj = 3.05, 95%CI: 2.26–4.12), as well as polymorphisms of CYP450 at rs1065852 (G/A vs G/G: ORadj = 1.46, 95%CI: 1.07–1.99; A/A vs G/G: ORadj = 1.63, 95%CI: 1.15–2.33) and rs16947 (A/A vs G/G: ORadj = 3.61, 95%CI: 2.09–6.23), were significantly associated with risk of total CHD in offspring. Similar results were also found for some subtypes of CHD. Additionally, significant interactions between maternal smoking and CYP450 genes on the risk of CHD were observed. Maternal smoking and CYP450 genetic variants were associated with increased risk of CHD and specific subtypes in offspring. And the effects of CYP450 genes on CHD may be modified by maternal smoking. Abstract : Supplemental Digital Content is available in the text